Absenteeism in the footwear industry in South Africa - Townsend, A C (Rhodes University, Faculty of Humanities, Department of Sociology, 1967)
From Introduction: During the past three decades or more, the study of absenteeism in industry has been carried on in many different ways, by numerous investigators and in a wide range of industries. The purpose of such studies has varied; sometimes they have been stimulated by purely academic interest and have sought to investigate the relationship between absenteeism and various other measurable factors in the work situation such as age, race, sex, length of service and wage rates. Most studies, however, have been prompted by the urgent necessity to determine whether an absence problem existed within a specific factory, community or industry and to discover some effective means of dealing with it. Most studies have been empirical and pragmatic as has befitted their intentions. Inevitably, those who have conducted studies of the latter type have asked two questions (a) how do the absence rates emerging from this investigation compare with those from other studies and (b) are they 'normal' or 'abnormal'? In other words, does the data which has been gathered indicate the existence of an absence problem? The main purpose of this monograph is to demonstrate that the Gross Absence Rate is not an effective basis for the discovery of answers to either of these questions. It will seek, in other words, to demonstrate the truth of the following fundamental postulate: THE GROSS ABSENCE RATE IS NOT, IN ITSELF, A SUFFICIENT BASIS FOR THE COMPARISON OF THE ABSENCE BEHAVIOUR OF ONE GROUP OF WORKERS WITH THAT OF ANOTHER OR WITH A PRE-ESTABLISHED NORM, NOR IS IT AN ADEQUATE INDICATOR OF THE PRESENCE OR OTHERWISE OF AN ABSENCE PROBLEM AMONG ANY GIVEN GROUP OF WORKERS. Although this study will include some account of investigations into the relationship between absence rates and various socio-economic factors, it will do so primarily in order to seek support for the above postulate.
Keywords: Absenteeism (Labor) -- South Africa; Footwear industry -- South Africa; Employees -- South Africa; South Africa -- Industries